Molecular investigation of pediatric portuguese patients with sensorineural hearing loss - Nogueira, C. (2011)
The understanding of the molecular genetics in sensorineural hearing loss (SNHL) has advanced rapidly during the last decade, but the molecular etiology of hearing impairment in the Portuguese population has not been investigated thoroughly. To provide appropriate genetic testing and counseling to families, we analyzed the whole mitochondrial genome in 95 unrelated children with SNHL (53 nonsyndromic and 42 syndromic) and searched for variations in two frequent genes, GJB2 and GJB6, in the non- syndromic patients. Mutations in mtDNA were detected in 4.2% of the cases, including a hitherto undescribed change in the mtDNA-tRNATrp gene (namely, m.5558A>G). We also identified mono- or biallelic GJB2 mutations in 20 of 53 non-syndromic cases and also detected two novel mutations (p.P70R and p.R127QfsX84). Our data further reinforce the notion that genetic heterogeneity is paramount in children with SNHL.